NREM Sleep Oscillations and Brain Plasticity in Aging - Fogel, Stuart; Martin, Nicolas; Lafortune, Marjolaine; Barakat, Marc; Debas, Karen; Laventure, Samuel; Latreille, Véronique; Gagnon, Jean-François; Doyon, Julien; Carrier, Julie (Frontiers in Neurology, 2012)
The human electroencephalogram (EEG) during non-rapid eye movement sleep (NREM) is characterized mainly by high-amplitude (> 75 µV), slow-frequency (< 4 Hz) waves (slow waves; SW) and sleep spindles (~11-15 Hz; > 0.25 s). These NREM oscillations play a crucial role in brain plasticity, and importantly, NREM sleep oscillations change considerably with aging. This review discusses the association between NREM sleep oscillations and cerebral plasticity as well as the functional impact of age-related changes on NREM sleep oscillations. We propose that age-related reduction in sleep-dependent memory consolidation may be due in part to changes in NREM sleep oscillations.